Detection of Aflatoxin M1 in the Milk of Naturally Grazed and on-farm-fed Camels - Khalifa, Marwa I.; Sallam, Khalid I.; Kasem, Nahed G. (Journal of Advanced Veterinary Research, 2023)
Aflatoxins (AFs) are mycotoxins produced by numerous species of Aspergillus. AFs contaminate agricultural commodities and thus feed and food including milk. So, this study aimed to assess the effect of the feeding type on the occurrence of AFM1 in camel milk. A total of 45 camel milk samples were obtained from the natural grazing herd in Shalatin (n= 20) and small scales farm breeding in Daraw (n= 25) in the period between September to December 2021. AFM1 levels were determined in these samples using the Vicam method. A significant difference was found between AFM1 levels in milk samples from herds of camels kept in a traditional environment (Natural grazing) and that in samples from camels in semi-intensive management systems (On-farm). Of note, all milk samples obtained from the nomadic area were free from AFM1, whereas, in the camel milk samples collected from a semi-intensive farm, AFM1 was reported in eight samples (32%) with 2 (8%) samples exceeding the EU Limits of 0.05 Âµg/ kg and 6 (24%) samples below such EU Limits. In conclusion, there was high contamination of milk samples obtained from camels reared on-farm with AFM1, while milk samples of camels naturally grazed were negative for AFM1. Therefore, milk hygiene from the farm, chilling, and distribution should be evaluated to reduce AFM1 levels in milk. Â 